1991
DOI: 10.1136/pgmj.67.790.754
|View full text |Cite
|
Sign up to set email alerts
|

Dose response to inhaled salbutamol in chronic obstructive airways disease

Abstract: Summary:High dose inhaled salbutamol is increasingly used in the management of chronic obstructive airways disease. To determine the range ofdoses to achieve optimal bronchodilatation and the proportion of patients requiring high dose therapy we have studied 23 patients with chronic obstructive airways disease. Cumulative dose responses were measured to six incremental doses of salbutamol (0. We conclude that in chronic obstructive airways disease there are wide individual variations in the dose of inhaledsalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Guidelines for managing an AECOPD generally agree that bronchodilators are considered first-line treatment24–26 but may not recommend a specific dose. In stable COPD it has been shown that 88% of patients achieved 90% of maximal bronchodilation with doses of inhaled salbutamol ≤1.2 mg 27. It could be argued that this pre-dosing with bronchodilators meant patients had already reached their maximum bronchodilator response before administration of magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for managing an AECOPD generally agree that bronchodilators are considered first-line treatment24–26 but may not recommend a specific dose. In stable COPD it has been shown that 88% of patients achieved 90% of maximal bronchodilation with doses of inhaled salbutamol ≤1.2 mg 27. It could be argued that this pre-dosing with bronchodilators meant patients had already reached their maximum bronchodilator response before administration of magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…33 Using higher doses, there is no substantial difference between using a short-acting beta-agonist or a short-acting muscarinic agonist. It has also been demonstrated that there is an effective improvement in FEV 1 on adding a high dose of salbutamol (600 μg) or a high dose of ipratropium bromide (120 μg) to regular tiotropium 34.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal dosing may contribute to the wide variation of responders with different degrees of reversibility, because dose-response relationships have been demonstrated. 33 Using higher doses, there is no substantial difference between using a short-acting beta-agonist or a short-acting muscarinic agonist. It has also been demonstrated that there is an effective improvement in FEV 1 on adding a high dose of salbutamol (600 μg) or a high dose of ipratropium bromide (120 μg) to regular tiotropium.…”
Section: Discussionmentioning
confidence: 99%
“…In stable COPD, earlier studies 10 have shown that 87% of maximal bronchodilation is achieved with an inhaled dose of 2 mg of terbutaline and 97% with a dose of 4 mg. In a larger group of stable COPD patients receiving albuterol, 87% of patients achieved 90% of their maximal bronchodilation (Emax) with doses of inhaled albuterol Յ 1.2 mg. 11 Whether such dose-response effects are applicable in AECOPD is unknown. Studies 12 in asthmatics have also shown that the bronchodilatory effect of ipratropium and terbutaline changes during the course of recovery from an exacerbation of asthma, with ipratropium becoming more effective as the patient recovers.…”
mentioning
confidence: 99%